2006
DOI: 10.1097/01.jom.0000205208.85800.70
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Blood Mercury Levels in Older Urban Residents

Abstract: These findings offer guidance for targeted education and possible new insights regarding the kinetics of mercury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…For example, fish consumption is beneficial to the prevention of cardiovascular diseases and Alzheimer disease; however, several reports have indicated that fish consumption was the major source of mercury exposure. [83][84][85][86] Mercury is present in three forms in the environment, including elemental or metallic mercury, inorganic mercury and organic mercury. The mercury compounds are generally used in dry-cell batteries, fluorescent bulbs, arc lamps, mirrors, and in the extraction of gold and silver from ores, thermometers, dental amalgam fillings and vaccine preserver.…”
Section: Mercurymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, fish consumption is beneficial to the prevention of cardiovascular diseases and Alzheimer disease; however, several reports have indicated that fish consumption was the major source of mercury exposure. [83][84][85][86] Mercury is present in three forms in the environment, including elemental or metallic mercury, inorganic mercury and organic mercury. The mercury compounds are generally used in dry-cell batteries, fluorescent bulbs, arc lamps, mirrors, and in the extraction of gold and silver from ores, thermometers, dental amalgam fillings and vaccine preserver.…”
Section: Mercurymentioning
confidence: 99%
“…Several studies, assessing populations who consume less than one fish meal per week, indicated that the average blood mercury level in adults was around 8 mg/L. [93][94][95][96] Latshaw et al 86 further analyzed the blood mercury content in older urban residents, and found that persons in the highest quartile of fish consumption had median mercury levels 1.82 times above the levels in the lowest quartile, while those in the highest education category had median mercury levels 1.57 times higher than levels in the lowest category. Moreover, a study in workers exposed to mercury cadmium telluride layers has shown that mercury value was estimated at 1.60 ± 0.20 mg Hg/L in control and at 10.72 ± 1.34 mg Hg/L in phase I and 8.08 ± 1.15 mg Hg/L in phase II; an individual who met with a mercury accident showed 226 mg Hg/L of blood.…”
Section: Mercurymentioning
confidence: 99%
“…Mercury is an environmental contaminant that has always been in the environment to a certain extent; however, modern industry has brought about an increase in prevalence in the environment (food, water, air, and medicine; Soares et al 2003; Latshaw et al 2006; Geier, Sykes, and Geier 2007). Mercury has been used in agriculture, as a preservative in vaccines, and medicinally, and released into the environment from coal burning and the production of chlorine.…”
Section: Discussionmentioning
confidence: 99%